Adoption Of Closed-loop Supply Chain Practices By Myhijau Mark Certified Manufacturing Firms In Malaysia: Antecedents, Constraints, Outcome And The Mediating Effect Of Green Capabilities - Siali, Fadilah (2023)
Closed-Loop Supply Chain (CLSC) acquires cores or product returns from consumers, recovering their residual value and remarketing them. The rapidness of economic growth gives manufacturers no option to shorten the product life cycle. Consequently, the new version of product upgrade happens too fast, hence increasing product returns in the form of End of Life (EOL) or end of use. This study formulates a research model to examine the antecedent factors which influenced, the constraints of the closed-loop supply chain practice as well as the impact on the triple bottom line in Malaysia. This research also explores the mediating effects of green capabilities on the relationship between the firm's external antecedents and its adoption of a closed-loop supply chain. To test the research hypotheses, a structural equation model has been used to survey the data drawn from MyHijau Mark certified directory in Malaysia. Hundred and nine companies have answered all seventy items questionnaire through purposive sampling. Therefore, this study has aimed to explain the relationship between Institutional Theory, Resource Based View, Natural Resource-Based View (NRBV) and Knowledge based view Theory towards a CLSC adoption in Malaysia. The findings highlighted the role of the government in overpowering competitors and customers in adopting a CLSC.